Pharmacotherapy for female sexual dysfunctions (FSDs): what is on the market and where is this field heading?. (2nd January 2023) - Nappi, Rossella E.; Tiranini, Lara; Cucinella, Laura; Martini, Ellis; Bosoni, David; Righi, Alessandra; Cassani, Chiara; Gardella, Barbara
ABSTRACT: Introduction: Female sexual dysfunctions (FSDs) are common in women of any age and have a huge impact on quality of life and relationships. They have a multifaceted etiology limiting the development of pharmacotherapies with a high rate of effectiveness. Safety issues are also a concern. Areas covered: The authors report the most recent advances in pharmacotherapy for premenopausal and postmenopausal women with a main focus on hypoactive sexual desire disorders (HSDD) and associated sexual symptoms. Good levels of evidence have emerged for psychoactive agents, such as flibanserin and bremelanotide, as well as hormonal compounds (transdermal testosterone). The authors also report briefly on intravaginal DHEA (prasterone), local estrogen therapy (LET), and ospemifene to manage effectively vulvovaginal atrophy/genitourinary syndrome of menopause (VVA/GSM). In addition, they discuss promising therapeutic options highlighting the main reasons that hamper the availability of new labeled products. Finally, they include the importance of the multimodal approach to address FSDs. Expert opinion: Approved pharmacotherapies for FSD are limited. Validated multidimensional instruments and adequate objective measures of physical and mental responses to sexual external and internal incentives are mandatory to identify women suitable to chronic or on-demand treatments and to assess their pattern of response in research and practice.